Parenting Styles as Predictors of Self-Esteem among Secondary School Students in Awka Education Zone, Anambra State (Journal of Guidance and Counselling Studies, 2025)
The development of self-esteem among secondary school students relies on supportive parenting and positive peer interactions, which together foster confidence, resilience, and emotional strength to handle academic and social challenges. This study investigated parenting styles as predictors of self-esteem among secondary school students in Awka Education Zone of Anambra State. The study was guided by three research questions and tested three null hypotheses at a 0.05 significance level using a predictive correlational survey research design. A multi-stage sampling method was employed to draw a sample of 840 students from a population of 5,028 senior secondary two (SS2) students from public secondary schools in Awka Education Zone of Anambra State. Two research instruments were adapted and used: Parenting Styles Questionnaire (PSQ) and Rosenberg Self-esteem Scale (RSES). A pilot test conducted with 40 SS2 students in Onitsha Education Zone produced strong internal consistency values: PSQ (α = 0.87), PPPS (α = 0.85), and RSES (α = 0.83). The instruments were administered directly to the participants. Regression analysis was applied to examine the predictive relationships between the variables and test the null hypotheses at 0.05 level of significance. The findings revealed that parenting styles (authoritative p = 0.795 (p > 0.05), authoritarian, p = 0.796 (p > 0.05) and permissive, p = 0.359 (p > 0.05) were not a significant predictor of the secondary school students’ self-esteem in Awka Education Zone of Anambra State. Based on these findings, it was recommended that school counsellors should adopt holistic strategies that take into account a range of other factors that influence self-esteem. These may include academic performance, emotional resilience, social competence, and mental health.